2023
DOI: 10.7759/cureus.37056
|View full text |Cite
|
Sign up to set email alerts
|

“Bariatric Beriberi”: A Rare Case of Wernicke Encephalopathy Two Weeks After Laparoscopic Sleeve Gastrectomy

Abstract: Wernicke encephalopathy (WE) is an acute neurological syndrome caused by thiamine (vitamin B1) deficiency. This disorder manifests as a triad of gait ataxia, confusion, and vision abnormalities. The absence of a full triad does not rule out WE. Because of its vague presentation, WE is commonly missed in patients with no history of alcohol abuse. Other risk factors for WE include bariatric surgery, hemodialysis, hyperemesis gravidarum, and malabsorption syndromes. WE is a clinical diagnosis that can be confirme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…Although this condition is likely underdiagnosed, Chang et al stated that WE occurs in less than 1% of all patients after receiving BS (15). According to Bathobakae et al, only approximately 15% of all WE cases are diagnosed antemortem due to the ambiguous set of neurological symptoms (9). Olmsted et al, in autopsy studies, revealed that up to 80% of cases of WKS are not diagnosed using the criteria of classical symptoms and signs, such as mental confusion, ocular signs, and ataxia.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although this condition is likely underdiagnosed, Chang et al stated that WE occurs in less than 1% of all patients after receiving BS (15). According to Bathobakae et al, only approximately 15% of all WE cases are diagnosed antemortem due to the ambiguous set of neurological symptoms (9). Olmsted et al, in autopsy studies, revealed that up to 80% of cases of WKS are not diagnosed using the criteria of classical symptoms and signs, such as mental confusion, ocular signs, and ataxia.…”
Section: Discussionmentioning
confidence: 99%
“…However, the clinical findings and the effectiveness of the treatment appeared to be sufficient for the diagnosis of WKS. Radiological examination by magnetic resonance imaging (MRI) can be used to confirm the diagnosis of WE (9). A positive test is characterized by hyperintensities in the periventricular areas of the mammillary bodies, thalamus, and periaqueductal and periventricular regions (9,11).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Micronutrient supplementation is often necessary, according to laboratory results. However, due to the unavailability of some vitamin dosages and uncertainty of the added clinical value of such dosages in many regions of the world, empirical supplementation is commonly recommended immediately, given the potential of vitamin deficiencies as a cause of hospital admission, such as thiamine deficiency for those in the late postoperative phase [24 ▪ ].…”
Section: Nutritional Management During Critical Illnessmentioning
confidence: 99%